2022
DOI: 10.3390/plants11202795
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Hydromulching and Arbuscular Mycorrhiza Improves Escarole Growth and Productivity by Regulating Nutrient Uptake and Hormonal Balance

Abstract: To improve water and nutrient use efficiencies some strategies have been proposed, such as the use of mulching techniques or arbuscular mycorrhizal fungi (AMF) inoculation. To gain insights into the interaction between the use of hydromulch and AMF inoculation on plant growth and productivity, escarole plants (Cichorium endivia, L.) were inoculated with the AMF Rhizophagus irregularis and grown with non-inoculated plants under different soil cover treatments: ecological hydromulching based on the substrate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Other authors [9], when using some of the hydromulches employed in this study (MS, RH, and WS) in escarole plants grown in small pots, observed few differences in the gas exchange parameters between mulched and non-mulched treatments in fully irrigated plants, although with deficit irrigation, the MS, RH, and polyethylene (PE) plants presented significantly higher g s than the plants grown in bare soil. In a recent study, Romero-Muñoz et al [10] attributed the highest gas exchange-related parameters in PEmulched plants to the physical properties of this material, arguing that the impermeability of PE blocked substrate evaporation, and, consequently, the plants had to increase stomatal opening to facilitate plant water (and gas) exchange, resulting in an increase in photosynthetic activity. In our study, the treatment most similar to PE with regard to physical properties would be RHL, although the previous argument did not result in a different behavior for this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors [9], when using some of the hydromulches employed in this study (MS, RH, and WS) in escarole plants grown in small pots, observed few differences in the gas exchange parameters between mulched and non-mulched treatments in fully irrigated plants, although with deficit irrigation, the MS, RH, and polyethylene (PE) plants presented significantly higher g s than the plants grown in bare soil. In a recent study, Romero-Muñoz et al [10] attributed the highest gas exchange-related parameters in PEmulched plants to the physical properties of this material, arguing that the impermeability of PE blocked substrate evaporation, and, consequently, the plants had to increase stomatal opening to facilitate plant water (and gas) exchange, resulting in an increase in photosynthetic activity. In our study, the treatment most similar to PE with regard to physical properties would be RHL, although the previous argument did not result in a different behavior for this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently concluded that escarole plants grown over hydromulches based on a rice husk, cereal straw, and mushroom substrate exhibited significantly improved growth under water stress conditions [9]. In the same crop, it was also found that hydromulch composed of mushroom by-products combined with the inoculation of a type of mycorrhizae improved the growth of escarole [10]. Using the same mixtures to test perennial weed emergence, it was observed that these materials reduced the appearance of certain weed species, confirming their potential to be used as a non-chemical weed control method [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the use of Bch affects the absorption of nutrients and water and causes an increase in RWC and a decrease in ion leakage under salinity stress conditions . Also, the combination of Bch and AMF improves growth and water absorption by inducing the expression of speci c genes and balancing plant hormones [52][53][54][55][56][57][58][59][60].…”
Section: Ion Leakage and Rwcmentioning
confidence: 99%
“…AMF inoculation can increase the production of plant growth hormones such as auxins, cytokinins, and gibberellins, which play a role in cell division and elongation [41][42][43]. Stem enlargement is affected by the presence of the hormones auxin and gibberellins [40,44].…”
Section: Amf Affects the Plant Growth Of Tomatoesmentioning
confidence: 99%